Effect of static electric field on luminescence spectra of quantum-size CdS, PbI2 particles and CdS monocrystals - RAKOVICH, YURY (My University, 1995)
The influence of static electric field on the luminescence spectra of quantum confined CdS and Pbl2 particles as well as bulk CdS monocrystals has been studied in this work. The applied electric field causes the increase in the excitonic luminescence intensity of quantum-sized CdS and Pbl2 particles accompanied with the spectral shift of their luminescence bands. Application of high electric field can follow to the field induced desorption of surface impurities, such as oxygen and reorganization of surface emitting states.
PUBLISHED
Keywords: electric field; Luminescence Spectra; CdS Monocrystals; Semiconductor; quantum-sized particle; CdS